The Influence Of Product Quality and Electronic Word Of Mouth On The Decision To Stay at Rumah Kayu Cottage Syariah in Bandung - Sindi Elvira Sagita; Aditya Yudanegara (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study aims to analyze the effect of product quality and electronic word of mouth on the decision to stay at Rumah Kayu Cottage Syariah Bandung. Data analysis using normality, correlation coefficient analysis, determination analysis, and simultaneous and partial hypothesis testing. The results of correlation coefficient analysis showed a result of 0.987 which means the relationship between product quality and electronic word of mouth to the decision to stay has a strong relationship. The coefficient of determination obtained in this study is 97.5%, meaning the influence of product quality and electronic word of mouth on the decision to stay, while the rest is influenced by other factors that were not studied in this study. Simultaneous hypothesis test conducted using the F-tiest obtained that the value of Fhitung of 1766.57 which is greater than the Ftabel for ? = 5% is 3.10 this means that simultaneously the quality of the product and the electronic word of mouth significant effect, while partially done using the T-test, shows that the quality of the product and the electronic word of mouth affect the decision to stay.